Ecophysiological responses of citrus trees and sugar accumulation of fruit in response to altered plant water relations - Prinsloo, Johan Andries (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Horticulture))--University of Stellenbosch, 2007.